OWE-031 Oesophageal aperistalsis is under investigated in those without achalasia or reflux. (8th June 2018) - Visaggi, Mr Pierfrancesco; Ibraheim, Hajir; Wong, Terry; Jafari, Jafar; Dunn, Jason; Zeki, Sebastian
Abstract : Introduction: Oesophageal aperistalsis (OA) is the absence of oesophageal motility with water swallows at high-resolution manometry (HRM). The main causes are achalasia and reflux although in many patients no cause is found, therefore we aimed to investigate the number of patients with an identifiable cause of OA and the number of patients in whom the most common aetiologies have been determined. There is no consensus for the investigation of OA without achalasia; this will depend on how common the underlying aetiology is. Methods: We examined the reports of patients who had HRM at Guy's and St. Thomas' NHS Trust from January 2008 to July 2017. 492 patients had OA as per the Chicago Classification 2014; achalasia was defined as an integrated relaxation pressure (IRP) of >15 mmHg or IRP 12–15 mmHg and a barium swallow or other imaging or a previous myotomy for achalasia was identified. For those without achalasia, Gastroesophageal reflux disease (GORD) was defined according to any pH study off PPI. Patients without GORD or achalasia were classified as non-achalasia, non-reflux aperistalsis (NANRA). Non-achalasia patients without a pH study were excluded (n≥35). The electronic patient record of NANRA patients was consulted to look for evidence of autoimmune disorders (AD), eosinophilic oesophagitis (EoE) or previous oesophageal surgery. Results: Among 457 included patients we defined three categories: 183 (40%) had achalasia, 185 (41%) had GORD and 89 (19%) had NANRA. Of the 89 NANRA patients, 29% had an AD including Systemic Lupus Erythematosus, Scleroderma, Sjögren syndrome and Antisynthetase syndrome (n≥25, M:F 3:7, average age ≥48). One had Myotonic Dystrophy (n≥1); 11% (n≥10) had hypersensitive oesophagus; 6% (n≥5) had surgery for atresia, oesophageal spasm, or gastric cancer; 2% (n≥2) had EoE and in 2% (n≥2) of patients AD screen and EoE screen were normal. The remaining 50% of NANRA patients (n≥44) had an unknown cause but incomplete investigations (no screen for AD: 97.7%; no biopsy: 67.4%). Conclusions: 1.The principal cause of OA is achalasia; it shouldn't be dismissed as a cause even if the IRP is <15 mmHg as 6.5% (n≥12) of patients with achalasia and OA had IRP <15 mmHg but typical radiological findings. 2.GORD is present in 41% of patients but it is unclear whether it is a cause or effect of OA, therefore the finding of GORD should not stop further investigation. 3.Patients with OA are under investigated for AD and EoE. 50% of patients with NANRA had incomplete investigations potentially losing the opportunity to identify other aetiologies. It is unclear whether NANRA patients should be routinely tested for AD or for EoE, or whether this should be done only in selected cases.